Constant and high switching frequency torque controller for DTC drives - Toh, C. L.; Nik Idris, N. R.; Yatim, Abdul Halim Mohamad (IEEE, 2005)
The letter presents a new method of increasing the switching frequency of a direct torque control (DTC) of induction machines. The method simply replaces the hysteresis comparator of the conventional DTC drives with a triangular waveform-based constant switching frequency controller. By synchronizing the digital signal processor (DSP) sampling with a triangular waveform and with an appropriate systematic controller design, a high switching frequency DTC drive is possible without requiring a high-frequency space-vector modulator. The implementation of the controller is simple and operates based on waveform comparisons; in this letter it is implemented using a combination of a DSP and a field programmable gate array device. Simulation and experimental results indicate that the controller both reduces the torque ripple and maintains a constant switching frequency